Pengaruh Fasilitas Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada CV Labanta Persada Bekasi - Harjanti, Safitri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Work facilities and the work environment can support the improvement of employee performance. This study aims to analyze the influence of work facilities and the work environment on employee performance at CV Labanta Persada Bekasi. Work facilities refer to the infrastructure and resources provided by the company, while the work environment includes both physical factors, such as lighting, ventilation, and cleanliness, as well as non-physical factors, such as relationships between employees and the work atmosphere. The research method used is a quantitative approach, with a population of 36 employees (respondents), which also serves as the sample. The sampling technique employed is saturated sampling. Data collection was done through observation, interviews, and questionnaires, with scoring based on a Likert scale. This study uses hypothesis testing with a t-test to determine whether independent variable have an effect on the dependent variable. The results of the analysis show that work facilities have a positive and significant impact on employee performance. Similarly, the work environment also has a positive and significant effect on employee performance. This study concludes that adequate work facilities and a conducive work environment are essential for improving employee performance. Therefore, companies are expected to continue enhancing work facilities and creating a work environment that supports optimal employee productivity.